2021
DOI: 10.1002/jsfa.11413
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the effects of kaolin on balancing berry phytohormones and quality attributes of Vitis vinifera grown in warm‐temperate climate regions

Abstract: BACKGROUND The application of kaolin particle film is considered a short‐term strategy against several environmental stresses in areas with a Mediterranean‐like climate. However, it is known that temperature fluctuations and water availability over the season can jeopardize kaolin efficiency in many Mediterranean crops. Hence, this study aims to evaluate the effects of kaolin foliar application on berry phytohormones, antioxidant defence, and oenological parameters at veraison and harvest stages of Touriga‐Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Some authors reported no effect or even an increase in net assimilation and stomatal conductance, while other researchers observed a reduction [42,43]. Based on this, the effectiveness of radiation-reflecting products in improving leaf resilience when subjected to severe environmental conditions, mainly through gas-exchange assessment, can be significantly changed according to the variety, water status, and stress severity [37]. The effects of these products suggest the modulation of indole-3-acetic acid (IAA), salicylic acid (SA), and abscisic acid (ABA) levels in crops cultivated in Mediterranean-type climates [37,44,45].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Some authors reported no effect or even an increase in net assimilation and stomatal conductance, while other researchers observed a reduction [42,43]. Based on this, the effectiveness of radiation-reflecting products in improving leaf resilience when subjected to severe environmental conditions, mainly through gas-exchange assessment, can be significantly changed according to the variety, water status, and stress severity [37]. The effects of these products suggest the modulation of indole-3-acetic acid (IAA), salicylic acid (SA), and abscisic acid (ABA) levels in crops cultivated in Mediterranean-type climates [37,44,45].…”
Section: Discussionmentioning
confidence: 92%
“…Thermal and water stresses are increasingly frequent in the Mediterranean production area during summer, limiting productivity and berry quality [8,33,34]. The exogenous foliar application of radiation-reflecting products has proven effective in mitigating the negative impacts of these abiotic stresses in grapevine and other fruit crops [15,[34][35][36][37]. However, to our knowledge, there is little available information about sunscreen foliar applications to mitigate thermal and water stress conditions in blueberries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is in this context that proper agronomic management together with the introduction of innovative and sustainable techniques assume great importance [24][25][26]. The present review paper examines multiple agronomic and canopy management techniques aimed at improving the aromatic quality of some of the most important aromatic white grape varieties grown all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…By consequence, short-term adaptation strategies, that allows to keep or improve plant growth regulation, should be studied under these environmental conditions [10,20]. Sunscreen materials that form an inert particle film upon the leaves, such as calcium carbonate, kaolin, and potassium silicate have been studied to increase reflective capacity, allowing leaf cooling, and reducing leaf and cluster sunburns under severe summer stress [24][25][26][27][28]. Shading nets produce a similar effect, and they are proposed as adaptation technique to mitigate the impacts of global warming in viticulture since limit the effects of high temperatures and to limit evapotranspiration [9].…”
Section: Introductionmentioning
confidence: 99%